MASS VACCINATION OF CHILDREN REDUCES FLU SICK RATE OF THE UNVACCINATED POPULATION - Yu.Z. Gendon (Union of pediatricians of Russia, 2007)
The author analyzes the efficiency of the children's mass vaccination against flu. It has been revealed that mass vaccination against flu reduces flu sick rate not only among the vaccinated children, but also within the general population. It reduces the frequency of hospitalizations related to complications, arising from influenzal infection, as well as death rate of elderly people caused by flu. The article highlights the economic efficiency estimation of the children's mass vaccination against flu.Key words: flu, sick rate, vaccination against flu, children.